2005
DOI: 10.1097/00001756-200505310-00009
|View full text |Cite
|
Sign up to set email alerts
|

Activation of c-Jun N-terminal kinase is required for neurite outgrowth of dopaminergic neuronal cells

Abstract: Recent studies indicate that activation of stress-activated protein kinases may be implicated in a broad range of biological activities including differentiation. To directly examine whether stress-activated protein kinases are involved in neuronal differentiation, we utilized retinoic acid-induced and spontaneous models of neurite outgrowth in dopaminergic neurons. Here, we show that retinoic acid-induced neurite outgrowth in MN9D dopaminergic neuronal cells was accompanied by activation of c-Jun N-terminal k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 14 publications
1
20
1
Order By: Relevance
“…5). Although others have implicated JNK in growth (Yao et al, 1997;Waetzig and Herdegen, 2003;Eom et al, 2005), our findings suggest that, in a single defined population of sensory neurons, this pathway does not significantly influence neurite growth per se. Other classes of neurons might respond differently.…”
Section: The Persistent Activation Of the Ap1 After Axotomy Occurs VIcontrasting
confidence: 75%
“…5). Although others have implicated JNK in growth (Yao et al, 1997;Waetzig and Herdegen, 2003;Eom et al, 2005), our findings suggest that, in a single defined population of sensory neurons, this pathway does not significantly influence neurite growth per se. Other classes of neurons might respond differently.…”
Section: The Persistent Activation Of the Ap1 After Axotomy Occurs VIcontrasting
confidence: 75%
“…These results were reinforced when similar data were obtained following siRNA knockdown of JNK1. Others have shown that the activation of JNK is required for neurite outgrowth in dopaminergic (11) and hippocampal (28,32) neurons. Jnk1 Ϫ/Ϫ mice had severe defects in the anterior commissure tract and a progressive loss of microtubules within axons and dendrites (5), demonstrating that JNK1 is required for the maintenance of neuronal microtubules.…”
Section: Discussionmentioning
confidence: 99%
“…JNK is a well-established downstream effector of Wnt/noncanonical signaling in the convergent extension/planar cell polarity pathway (34). It also has been identified as a key mediator of neurite outgrowth (11,28), specifically functioning in Wnt-7b-dependent, Dvl/Rac-mediated dendritic arborization (32). To examine the potential role of JNK in Wnt-dependent neurite outgrowth, we first sought evidence of the activation of JNK following the exposure of TC-32 cells to Wnt-3a.…”
Section: Vol 28 2008 Wnt-3a and Dkk1 Induce Neurite Outgrowth In Esmentioning
confidence: 99%
See 1 more Smart Citation
“…Nonetheless, deletion of a single isoform, JNK1, disrupts axon tract maintenance in vivo (Chang et al 2003;Bjorkblom et al 2005). The role of JNKs in axonal polarity and initiation is further supported by many cell culture studies showing that JNK inhibition attenuates neuritogenesis (Leppa et al 1998;Waetzig and Herdegen 2003;Eom et al 2005;Oliva et al 2006;Newbern et al 2007). Numerous lines of evidence suggest this pathway is also important for axonal extension (Leppa et al 1998;Rosso et al 2005;Xiao et al 2006;Ciani and Salinas 2007;Eminel et al 2008).…”
Section: Jnk Signaling and Axon Elongationmentioning
confidence: 96%